IMPLEMENTATION OF REMOTE AUDITING : A LITERATURE REVIEW - Wardhani, Yovita Kusuma; Rochayatun, Sulis (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The threat of bankruptcy for companies due to the Covid-19 pandemic has made many companies commit fraud by manipulating data and recording in their financial statements so that the value of their income increases. This is a challenge for auditors in carrying out their duties to assess the fairness of financial statements. Moreover, access restrictions cause auditors to be unable to come directly to the location to carry out the audit process. The option that can be done by the auditor team so that they can still conduct an examination without having to meet in person is a remote audit. This study aims to find out, analyze, explain, and reveal how the effectiveness of the implementation of remote audits as a result of the Covid-19 pandemic. This research uses qualitative methods with literature review techniques. The data used is secondary data sourced from articles, journals, and previous studies that are relevant and related to the topic or title of this research. This study found that the existence of access restrictions causes auditors to be unable to come directly to the location to carry out the audit process. The implementation of remote audit is considered effective for auditors because it provides many benefits for auditors in conducting the audit process remotely. However, keep in mind that remote auditing also has its own disadvantages, so it is necessary to reconsider the decision to use remote auditing.Remote Audit, Implementation, Literature Review